A Wearable Mixed Reality Platform to Augment Overground Walking: A Feasibility Study - Evans, Emily; Dass, Megan; Muter, William M.; Tuthill, Christopher; Tan, Andrew Q.; Trumbower, Randy D. (Frontiers in Human Neuroscience, 2022)
Humans routinely modify their walking speed to adapt to functional goals and physical demands. However, damage to the central nervous system (CNS) often results in abnormal modulation of walking speed and increase risk of falls. There is considerable interest in pursuing therapies that incorporate augmented sensory feedback devices to compensate for less reliable signaling within the CNS after injury or disease. Augmented visual feedback uses a range of immersive environments to enhance walking ability after injury to the CNS. Fully immersive virtual reality technologies show benefits in boosting training-related gains in walking performance; however, they lack views of the real world that may limit functional carryover. Mixed reality provides partially immersive environments to extend the virtual reality benefits of interacting with virtual objects but within an unobstructed view of the real world. Despite this potential advantage, the feasibility of using a wearable MR head mount device (MR-HMD) for visual feedback to prompt goal-directed changes in overground walking speed remains unclear. Thus, we developed and evaluated a novel mixed reality application using the Microsoft HoloLens MR-HMD to augment visual feedback during overground walking in a cohort of able-bodied adults. This platform provided real-time visual cues related to each participant’s self-selected walking speed. Participants walked with MR-HMD visual feedback at 85%, 100%, and 115% of their baseline self-selected speed. We block-randomized the order of these feedback conditions. Walking performance corresponded to the accuracy and variability of three walking parameters (speed, stride length, and stride time) within and between the feedback conditions. Overall, participants matched their overground walking speed to the target speed of the MR-HMD visual feedback conditions (all p-values > 0.05). Walking speed variability did not differ between walking with and without visual feedback. However, stride length and time variability increased with visual feedback as compared to without feedback. The findings offer support for MR-based visual feedback as a method to provoke goal-specific changes in overground walking behavior. Further studies are necessary to determine the clinical safety and efficacy of this MR-HMD technology to provide extrinsic sensory feedback in combination with traditional treatments in rehabilitation.